Phytochemical Investigation & Diuretic Activity of Tecoma Stans Leaf Extract - Aftab Shaikh,; Dr. Pradnya Jagtap,; Dr. Ashish Chimbalkar,; Vaishnavi Kharat,; Shraddha Shinde,; Dr. Bapuso Yadav,; Priyanka Devhare,; Dr. Makarand Puri,; Dhanshri Shinde,; Dr. Devendra Shirode,; Dr. Aniket Garud, (The Bioscan, 2025)
Tecoma stans leaves were collected, dried, and processed to obtain a Hydroethanolic extract using percolation. The extract was then administered to adult male Wistar rats in varying doses (250 mg/kg, 375 mg/kg, and 500 mg/kg) to evaluate its diuretic activity over 14 days. Furosemide, a standard diuretic drug, served as the positive control. Urine volume, pH, and diuretic index were measured on days 1st, 7th, and 14th. Histopathological examinations of kidney and liver tissues were conducted post-experiment. Additionally, molecular docking studies were performed to understand the binding interactions of the extract's bioactive compounds with target proteins. The study demonstrated that the Hydroethanolic extract of Tecoma stans significantly increased urine output in a dose-dependent manner. The highest dose (500 mg/kg) produced a diuretic index of 4.80 and a Lipschitz value of 0.65 on the 14th day, indicating potent diuretic activity comparable to the standard drug furosemide. Histopathological analysis revealed no adverse effects on the kidneys and liver. Molecular docking studies suggested strong binding affinities of the extract's bioactive compounds with diuretic target proteins. Tecoma stans leaf extract exhibits significant diuretic activity, suggesting its potential as a natural alternative for managing body fluids. Further research is warranted to isolate specific bioactive compounds and elucidate their mechanisms of action.